Analisis Dampak Konflik Lahan terhadap Masyarakat Adat Sihaporas dalam Perspektif Ekologi Politik: Studi Kasus PT Toba Pulp Lestari di Kecamatan Pematang Sidamanik - Yenita Ekasanti Sidabalok; Muliono Muliono; Galank Pratama (International Forum of Researchers and Lecturers, 2026)
Land conflict between the Sihaporas indigenous community and PT Toba Pulp Lestari (TPL) remains an ongoing agrarian issue that directly affects the community’s livelihoods. The inclusion of the company’s concession within the customary territory has changed patterns of land control and use that were previously managed collectively across generations. This situation restricts access to agricultural land and forests, reduces sources of income, and creates social tensions and confrontations. This study aims to analyze the impacts of land conflict on the Sihaporas indigenous community and to examine the conflict through a political ecology perspective with a focus on power relations among actors. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that the conflict affects economic, social, and cultural aspects of the community and reflects unequal power relations between indigenous peoples, corporations, and the state in controlling agrarian resources.